ANALISIS GENDER DAN HUKUM TERHADAP KONSTRUKSI GURU PEREMPUAN SEBAGAI PELAKU ASUSILA DENGAN KORBAN ANAK LAKI-LAKI DALAM KOMENTAR NETIZEN YOUTUBE: STUDI KASUS DI KABUPATEN GROBOGAN - Endang Astuti; Sri Suciati (STKIP Subang, 2025)
Cases of sexual misconduct involving female teachers and male child victims in Grobogan Regency have attracted widespread public attention, particularly through news coverage on YouTube that has generated extensive netizen commentary. This study aims to examine how gender and legal constructions are produced in netizens’ comments regarding female teachers as perpetrators and male children as victims. Employing a qualitative approach, this research applies critical discourse analysis and digital netnography. The analysis focuses on representations of perpetrators and victims, gender bias, power relations, and legal interpretations embedded in digital public discourse. The findings reveal that netizen comments tend to reproduce gender-based stigmatization toward female teachers through moral labeling, social judgment, and the neglect of the presumption of innocence. Meanwhile, male child victims are not consistently positioned as vulnerable subjects but are often framed within ambiguous narratives that diminish the seriousness of sexual violence. Keywords: gender, law, netizen comments